PROYEKSI KEBUTUHAN AIR BERSIH PDAM WAY SEKAMPUNG DI KECAMATAN BANYUMAS PADA TAHUN 2045 - Naiya Giska Fauzhia Sekar Arum; Hardoyo Hardoyo; Natalina Natalina (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Water is one of the most important sources of life for all living things on earth, however, not all people have the ability to treat water, especially at PDAM Way Sekampung in the service area of Banyumas District, so this practical work is carried out with the aim of finding out how much clean water needs are needed to meet the needs of PDAM Way Sekampung in the Banyumas District Service Area for the next 20 years with the research methods used Namely by collecting primary and secondary data, then the population projection calculation for the next 20 years is carried out using 3 methods, namely the arithmetic method, the geometric method, and the least square method. The need for clean water that is calculated is domestic needs, non-domestic needs, and water loss. The results of the projection of the amount of clean water needs in Banyumas District in the next 20 years were obtained in total of 23.21 liters/second with domestic water needs of 16.0 liters/second, non-domestic water needs of 7.20 liters/second. Based on data from PDAM Way Sekampung the total installed capacity is currently 60 liters/second. So that in 2045 the current installed capacity will still be sufficient for the next 20 years.